2015
DOI: 10.1021/acs.inorgchem.5b00803
|View full text |Cite
|
Sign up to set email alerts
|

A Complexation Study of 2,6-Bis(1-(p-tolyl)-1H-1,2,3-triazol-4-yl)pyridine Using Single-Crystal X-ray Diffraction and TRLFS

Abstract: To develop a selective ligand for the separation of lanthanides(III) and actinides(III) the coordination chemistry of the chelating N-donor ligand 2,6-bis(1-(p-tolyl)-1H-1,2,3-triazol-4-yl)pyridine (BTTP) was investigated. The two isostructural lanthanide compounds [Ln(BTTP)3(OTf)3] (Ln = Eu (1), Sm (2); OTf = trifluoromethanesulfonate) were synthesized and fully characterized. The solid-state structures of both compounds were established by single-crystal X-ray diffraction. The complexation of Cm(III) and Eu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…The log β values are higher for Am 3+ than for the Ln 3+ ions studied, indicating the selectivity of this class of ligands for Am 3+ over the Ln 3+ ions. In the cases of terdentate N‐donor ligands, namely BTP, PyTri derivatives, however, higher stoichiometric complexes were observed for Am 3+ than for the Ln 3+ ions.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The log β values are higher for Am 3+ than for the Ln 3+ ions studied, indicating the selectivity of this class of ligands for Am 3+ over the Ln 3+ ions. In the cases of terdentate N‐donor ligands, namely BTP, PyTri derivatives, however, higher stoichiometric complexes were observed for Am 3+ than for the Ln 3+ ions.…”
Section: Resultsmentioning
confidence: 93%
“…Lewis et al explored a bis(1,2,4‐triazinyl)phenanthroline (R‐BTPhen; Figure ) derivative also for this purpose . Bis(triazolyl)pyridines (PyTri; Figure ) are another class of ligands, which were also explored for the selective extraction and complexation studies of the trivalent actinides over the lanthanides . Keifer et al[23a] have synthesized a p ‐tolyl derivative of PyTri for the selective complexation/extraction of An 3+ over Ln 3+ .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, tridentate N ligands of the 2,6‐bis(triazolyl)pyridine type exhibited particular selectivity for Am III . Kiefer et al examined the complexation behaviors of 2,6‐bis[1‐( p ‐tolyl)‐1 H ‐1,2,3‐triazol‐4‐yl]pyridine (BTTP) with Eu III , Sm III , and Cm III ions through single‐crystal X‐ray diffraction and time‐resolved laser fluorescence spectroscopy (TRLFS) . Afterwards, Macerata et al found that hydrophilic clicked 2,6‐bis(triazolyl)pyridines could selectively strip the actinides from a diglycolamide‐containing kerosene solution into an acidic aqueous phase .…”
Section: Introductionmentioning
confidence: 99%